2023
DOI: 10.1155/2023/8215567
|View full text |Cite
|
Sign up to set email alerts
|

T Cell Subsets and the Expression of Related MicroRNAs in Patients with Recurrent Early Pregnancy Loss

Abstract: This study explored the role of T cell subsets and the expression of related microRNAs in patients with recurrent early pregnancy loss (EPL). Fifty patients with EPL loss between May 2018 and May 2021 were randomly selected as the EPL group, and 50 pregnant women with normal pregnancies or normal delivery outcomes were randomly selected as the control group. The expression levels of T cell subset-related markers and T cell subset-related miRNAs, in addition to the frequencies of T cell subsets, in peripheral b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…The expression of miR-155 was also studied by Yan et al in T-cells, as well as by Li et al in NK cells of the endometrium of women with a history of recurrent miscarriages. The results of the two studies are aligned on increased expression of miR-155 in women who experienced miscarriages, and the authors suggest the possibility of using this miRNA as a possible future biomarker for recurrent miscarriage prognosis and treatment strategies [ 14 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The expression of miR-155 was also studied by Yan et al in T-cells, as well as by Li et al in NK cells of the endometrium of women with a history of recurrent miscarriages. The results of the two studies are aligned on increased expression of miR-155 in women who experienced miscarriages, and the authors suggest the possibility of using this miRNA as a possible future biomarker for recurrent miscarriage prognosis and treatment strategies [ 14 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, Yan et al reported decreased expression of miR-146a in women with recurrent miscarriages. Moreover, the authors suggested that the decreased expression of miR-146a can be used as a diagnostic biomarker of miscarriage [ 26 ]. The need for further studies of miR-146a and its association with miscarriages should be highlighted.…”
Section: Discussionmentioning
confidence: 99%
“…This specific role of Tregs is to maintain homeostasis during pregnancy by suppressing the activation of autoreactive or alloreactive effector T cells through a diverse repertoire of molecular mechanisms [24,25]. The application of Treg epitopes capable of inducing tolerance seems to be a promising approach for the treatment of immunological causes of pregnancy loss [26,27]. Moreover, the lack of immunogenicity of Treg epitopes in vivo means that they should prove safe for future clinical applications in humans [28,29].…”
mentioning
confidence: 99%